PERSEPSI MASYARAKAT TENTANG WANITA PEKERJA BURUH TANI DI KENAGARIAN TANAH BAKALI INDERAPURA KECAMATAN AIRPURA KABUPATEN PESISIR SELATAN - Afdhal, Dayu Maida (STKIP PGRI Sumbar, 2014)
This Reseacht of aims to determine the Public Perceptions About Women Workers Peasants in village Tanah Bakali Inderapura District Airpura Pesisir Selatan District views of: 1) a low in Village Community Education Bakali Inderapura Land District of Airpura 2). Low income in village Bakali Inderapura Land District of Airpura 3). The skills that people have less in village Bakali Inderapura Land District of Air pura. Type of research that qualitative research. Data were collected through observation, interviews, documentation. Informants in this study is the Chairman of Farmers Group, Community Leaders, Women Peasants and People living near village Land Bakali Inderapura. The results of the research in the Land village Bakali Inderapura District of Airpura found that: 1). Education of women workers are still many farm workers whose education is still low as only finished primary school and even elementary school. 2). Income working women farm workers is still low this because they earn less wages making it difficult for them to meet the needs of everyday life 3). Lack of skills possessed by women workers farm workersmaking them only work as a laborer and farmer activities.